Preparation of Turkey Skeleton by Boiling Method - Hamid, Asadullah (Journal of Natural Sciences – Kabul University, 2023)
Turkey is a domestic bird that has important role in economy. Meat and eggs can be used as a daily nutrient. The skeleton of the turkey is very simple and precise compare to domestic mammals. The skeleton of the turkey had high level of calcium and phosphorus. The purpose of this research work is to prepare a turkey skeleton by boiling method and find anatomical differences of its skeleton. In this work a turkey is slaughtered by Islamic way and prepared its skeleton by boiling technique. The results of this research shows that the skeleton of the turkey has some species specific variation. The lumbar vertebrae of the turkey is fused with sacrum and there is no pubic symphysis in the skeleton. Turkey has wide and big keel and coxae compare to other domestic birds.